Ruthenium indenylidene “1st generation” olefin metathesis catalysts containing triisopropyl phosphite - Guidone, Stefano; Nahra, Fady; Slawin, Alexandra M. Z.; Cazin, Catherine S. J. (Beilstein Journal of Organic Chemistry, 2015)
The reaction of triisopropyl phosphite with phosphine-based indenylidene pre-catalysts affords “1st generation” cis-complexes. These have been used in olefin metathesis reactions. The cis-Ru species exhibit noticeable differences with the trans-Ru parent complexes in terms of structure, thermal stability and reactivity. Experimental data underline the importance of synergistic effects between phosphites and L-type ligands.
Keywords: 1st generation; indenylidene; metathesis; phosphite; ruthenium

(untitled) - Hoveyda, A. H.; Zhugralin, A. R. (Nature, 2007)

(untitled) - Chauvin, Y. (Angew. Chem., Int. Ed., 2006)

(untitled) - Schrock, R. R. (Angew. Chem., Int. Ed., 2006)

(untitled) - Grubbs, R. H. (Angew. Chem., Int. Ed., 2006)

(untitled) - Fürstner, A. (Angew. Chem., Int. Ed., 2000)

(untitled) - Buchmeiser, M. R. (Chem. Rev., 2000)

(untitled) - Connon, S. J.; Blechert, S. (Angew. Chem., Int. Ed., 2003)

(untitled) - Grubbs, R. H.; Miller, S. J.; Fu, G. C. (Acc. Chem. Res., 1995)

(untitled) - Nicolaou, K. C.; Bulger, P. G.; Sarlah, D. (Angew. Chem., Int. Ed., 2005)

(untitled) - Trnka, T. M.; Grubbs, R. H. (Acc. Chem. Res., 2001)

(untitled) - Schrock, R. R.; Hoveyda, A. H. (Angew. Chem., Int. Ed., 2003)

Handbook of Metathesis: Catalyst Development - Grubbs, R. H. (Wiley-VCH, 2003)

Olefin Metathesis – Theory and Practice - Grela, K. (Wiley-VCH, 2014)

(untitled) - Nguyen, S. T.; Johnson, L. K.; Grubbs, R. H.; Ziller, J. W. (J. Am. Chem. Soc., 1992)

(untitled) - Nguyen, S. T.; Grubbs, R. H.; Ziller, J. W. (J. Am. Chem. Soc., 1993)

(untitled) - Schwab, P.; Grubbs, R. H.; Ziller, J. W. (J. Am. Chem. Soc., 1996)

(untitled) - Boeda, F.; Clavier, H.; Nolan, S. P. (Chem. Commun., 2008)

(untitled) - Weskamp, T.; Kohl, F. J.; Herrmann, W. A. (J. Organomet. Chem., 1999)

(untitled) - Huang, J.; Schanz, H.-J.; Stevens, E. D.; Nolan, S. P. (Organometallics, 1999)

(untitled) - Scholl, M.; Ding, S.; Lee, C. W.; Grubbs, R. H. (Org. Lett., 1999)

(untitled) - Sanford, M. S.; Love, J. A.; Grubbs, R. H. (J. Am. Chem. Soc., 2001)

(untitled) - Clavier, H.; Nolan, S. P. (Chem. – Eur. J., 2007)

(untitled) - Monsaert, S.; Drozdzak, R.; Dragutan, V.; Dragutan, I.; Verpoort, F. (Eur. J. Inorg. Chem., 2008)

(untitled) - Nelson, D. J.; Manzini, S.; Urbina-Blanco, C. A.; Nolan, S. P. (Chem. Commun., 2014)

(untitled) - Bantreil, X.; Schmid, T. E.; Randall, R. A. M.; Slawin, A. M. Z.; Cazin, C. S. J. (Chem. Commun., 2010)

(untitled) - Schmid, T. E.; Bantreil, X.; Citadelle, C. A.; Slawin, A. M. Z.; Cazin, C. S. J. (Chem. Commun., 2011)

(untitled) - Songis, O.; Slawin, A. M. Z.; Cazin, C. S. J. (Chem. Commun., 2012)

(untitled) - Bantreil, X.; Poater, A.; Urbina-Blanco, C. A.; Bidal, Y. D.; Falivene, L.; Randall, R. A. M.; Cavallo, L.; Slawin, A. M. Z.; Cazin, C. S. J. (Organometallics, 2012)

(untitled) - Urbina-Blanco, C. A.; Bantreil, X.; Wappel, J.; Schmid, T. E.; Slawin, A. M. Z.; Slugovc, C.; Cazin, C. S. J. (Organometallics, 2013)

(untitled) - Falivene, L.; Poater, A.; Cazin, C. S. J.; Slugovc, C.; Cavallo, L. (Dalton Trans., 2013)

(untitled) - Guidone, S.; Songis, O.; Nahra, F.; Cazin, C. S. J. (ACS Catal., 2015)

(untitled) - Guidone, S.; Songis, O.; Falivene, L.; Nahra, F.; Slawin, A. M. Z.; Jacobsen, H.; Cavallo, L.; Cazin, C. S. J. (ACS Catal., 2015)

(untitled) - Bantreil, X.; Cazin, C. S. J. (Monatsh. Chem., 2015)

N-Heterocyclic Carbenes in Transition Metal Catalysis and Organocatalysis - Cazin, C. S. J. (Springer, 2011)

(untitled) - Ung, T.; Hejl, A.; Grubbs, R. H.; Schrodi, Y. (Organometallics, 2004)

(untitled) - Slugovc, C.; Burtscher, D.; Stelzer, F.; Mereiter, K. (Organometallics, 2005)

(untitled) - Ho, C.-Y.; Jamison, T. F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Wallace, D. J.; Reamer, R. A. (J. Org. Chem., 2014)

(untitled) - Chatterjee, S.; Guchhait, S.; Goswami, R. K. (J. Org. Chem., 2014)

(untitled) - Keck, C. G.; Kendall, J. L.; Caster, K. C. (Adv. Synth. Catal., 2007)

(untitled) - Hong, S. H.; Day, M. W.; Grubbs, R. H. (J. Am. Chem. Soc., 2004)
Phosphorus ylide bearing the alkylidene moiety has already been proposed.

(untitled) - Terada, Y.; Arisawa, M.; Nishida, A. (Angew. Chem., Int. Ed., 2004)

(untitled) - Kirkland, T. A.; Grubbs, R. H. (J. Org. Chem., 1997)